A ocorrência dos mamíferos na Mata Atlântica oriental: do passado ao presente - Moreira, Danielle de Oliveira (2013)
It is known that human activities have caused major changes in many ecosystems, affecting the overall diversity of species. But there is a great urgency to understand how these activities historically has been influencing the persistence of organisms. Species’ studies of occurrence in historical times is a mean in indicating changes in the distribution patterns of species and also indicate human influence on the vulnerability of these populations. Historical research using old publications provide detailed descriptions of the occurrence of species throughout centuries, especially in periods prior to humans settlements. We conducted a study of large mammals in the Atlantic Forest, using publications from the sixteenth, seventeenth, eighteenth and nineteenth centuries to access records unknown or ignored by science, and we compared with recent records. We aimed (1) retrieve information on the identity and geographical distribution of large mammals, mapping scientific knowledge of the first centuries of Brazilian colonization, (2) identify patterns of range contractions caused by regional extinctions; and (3) indicate which are the main intrinsic and extrinsic factors that increase the vulnerability of extinction of large mammals in the Atlantic Forest. Among theold publications, we recognize at least 45 taxa of large mammals mentioned by the authors. We found that many of the descriptions made between the sixteenth and seventeenth centuries were recorrents, indicating that the information came from similar sources (e.g. indigenous culture, observations of precedents foreign visitors). Due to the evolution of science, the contribution of the nineteenth’s naturalists was more systematic bringing more information about mammals diversity and distribution. In order toidentify patterns in mammals’ occurrence and range contractions, we compared old and current occurrences records of 29 species Atlantic Rainforest. For five species we found that historical range is larger than in documented literature. Sixteen of the species had their ranges contracted, and nine lost over than 50% of its historical range. Because many of the Atlantic Forest large mammals are at risk of extinction, we indicated what are the main intrinsic and extrinsic factors that increase the vulnerability of these species. We use phylogenetic comparative methods and logistic regression analysis and assessed the spatial and temporal pattern of historical records of mammals. Mammals with slow reproductive characteristics were particularly vulnerable. Furthermore, for five species, human population density has influenced their recent occurrences. Historical analyses like this reveal possible regional extinction of species in a simple way, especially when they are not readily apparent. These results can be viiiused to improve our knowledge of historical conditions of the species and in future planning studies and management of large mammals